PERBANDINGAN KUALITAS SUHU RUANG DAN SUHU LEMARI PENDINGIN DITINJAU DARI TINGGI KANTUNG HAWA, INDEKS KUNING TELUR, INDEKS ALBUMIN, HAUGH UNIT DAN CEMARAN TELUR PUYUH YANG DISIMPAN PADA MIKROBA - Gabryella F. Amalo; Annytha I. R. Detha; Diana A. Wuri (Jurnal Veteriner Nusantara, 2016)
Quail egg is one of animal product coming from poultry livestock which many people consume it and have higher nutrition than chicken’s egg. Quality of quail egg can be influenced by temperature and keeping time. This research aims to know the comparison of quail egg quality which stored at room temperature and refrigerator temperature to air sac egg, yolk index, albumin index, Haugh Unit and Total Plate Count (TPC). Samples counted 36 quail eggs which 0 old. This research using 6 keeping variation long (7, 10, 13, 16, 19 and 20 days), 2 temperatures (30 ºC- 32 ºC and 4 ºC) with 3 time restating. The results are the best keeping time of quail egg which stored at room temperature is under 7 days and under 7 days too for refrigerator temperature. Based on air sac egg, yolk index, albumin index and Haugh Unit, quail egg which stored at refrigerator temperature have better quality than room temperature. Even though, based on TPC, the quality of both are same. The conclusion is quail egg which stored at room temperature and refrigerator temperature is save to consume if the age of egg is under 7 days.